Advances in early identification of children and adolescents at risk for psychiatric illness. Issue 6 (November 2020) - Raballo, Andrea; Poletti, Michele
Abstract : Purpose of review: Childhood and adolescence are a crucial time window for the early identification of perspectival risk for adult psychopathology. This article reviews current advances in the field. Recent findings: Converging developmentally focused and predictive approaches are rapidly expanding in the field of early identification of children and adolescents at risk for psychiatric illness. Although the former emphasizes early phenotypic trajectories emerging in childhood and adolescence, the latter operate in terms of clinical risk staging. Decisive advances in the field include the metaanalytical evidence of the predictive value of clinical high-risk criteria in childhood–adolescence; the systematization of premorbid manifestations of psychotic vulnerability and bipolar prodromes; the corroboration of certain sets of anomalous subjective experiences as transdiagnostic index of familial genetic risk (i.e., basic symptoms) and early developmental expression of schizophrenia spectrum vulnerability (i.e., self-disorders). Summary: Childhood phenotypic manifestations of liability to mental disorders are often cooccurrent and undergo a plastic, heterotypic modification along the transition to adolescence. In general, they represent epiphenomenic flags of a broad vulnerability for the subsequent structuration of mental illness. This perspective coheres with the p -factor model of psychopathology and complements the clinical staging model which informs the early detection paradigm of severe mental disorders.